2010
DOI: 10.1002/micr.20813
|View full text |Cite
|
Sign up to set email alerts
|

From simple interrupted to complex spiral: A systematic review of various suture techniques for microvascular anastomoses

Abstract: Accomplishing successful microvascular anastomoses is undoubtedly one of the most critical steps in performing free tissue transfer. However, the ideal technique has often been a subject of debate. Therefore, our objective was to review the current literature in an attempt to find objective evidence supporting the superiority of one particular technique. A PubMed and OVID on-line search was performed in November 2007 using the following keywords: microvascular anastomoses, microsurgical anastomosis, continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 40 publications
2
50
1
2
Order By: Relevance
“…They weighed 200-320g and were kept in a controlled environment with food and water ad libitum. The sample size was determined at the beginning of the study through specific statistical tests, based in previous studies [6][7][8][9] . The risk management standards α (5%) and β (10%) were considered, as well as the diversity of variables.…”
Section: ■ Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…They weighed 200-320g and were kept in a controlled environment with food and water ad libitum. The sample size was determined at the beginning of the study through specific statistical tests, based in previous studies [6][7][8][9] . The risk management standards α (5%) and β (10%) were considered, as well as the diversity of variables.…”
Section: ■ Methodsmentioning
confidence: 99%
“…Mainly, because studies until 1960s demonstrated the superiority of this technique over the others suturing technique. However, after 1970s, a lot of studies refuted this data and reported similar patency rates using a continuous suture technique [4][5][6][7] .…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations